2013
DOI: 10.1016/j.trsl.2012.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Current status of gene therapy for brain tumors

Abstract: Glioblastoma (GBM) is the most common and deadliest primary brain tumor in adults, with current treatments having limited impact on disease progression. Therefore the development of alternative treatment options is greatly needed. Gene therapy is a treatment strategy that relies on the delivery of genetic material, usually transgenes or viruses, into cells for therapeutic purposes, and has been applied to GBM with increasing promise. We have included selectively replication-competent oncolytic viruses within t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 174 publications
(174 reference statements)
0
39
0
Order By: Relevance
“…[23][24][25] Reviews of boron neutron capture therapy, brachytherapy, high-intensity focused ultrasound (HiFU), gene therapy, laser interstitial thermal therapy, proton beam radiotherapy, oncolytic viruses, and pulsed electric fields are available elsewhere. 7,[26][27][28][29][30][31][32][33][34] These therapeutic approaches are not mutually exclusive. For example, because many molecularly targeted chemotherapeutics, gene-bearing vectors, and boron delivery agents are high-molecular-weight structures that cannot penetrate the BBB when administered systemically, they require delivery by a method that bypasses or disrupts the BBB, such as CED or HiFU.…”
Section: Introductionmentioning
confidence: 99%
“…[23][24][25] Reviews of boron neutron capture therapy, brachytherapy, high-intensity focused ultrasound (HiFU), gene therapy, laser interstitial thermal therapy, proton beam radiotherapy, oncolytic viruses, and pulsed electric fields are available elsewhere. 7,[26][27][28][29][30][31][32][33][34] These therapeutic approaches are not mutually exclusive. For example, because many molecularly targeted chemotherapeutics, gene-bearing vectors, and boron delivery agents are high-molecular-weight structures that cannot penetrate the BBB when administered systemically, they require delivery by a method that bypasses or disrupts the BBB, such as CED or HiFU.…”
Section: Introductionmentioning
confidence: 99%
“…Although the high levels of EGFR in some forms of GBM also make it an accurate and desirable therapeutic target, current therapies targeting EGFR, including tyrosine kinase inhibitors and RNA interference, have proved to be ineffective [7,8,34]. Therefore, attention is being addressed to other means: the delivery of novel antitumor agents across the blood-brain barrier, gene therapy, and brain tumor vaccines [35][36][37]. One study found that the use of metallic nanoparticles conjugated to anti-EGFR antibody combined with cisplatin could eradicate tumor cells when subjected to radiation in vitro [38].…”
Section: Discussionmentioning
confidence: 99%
“…61 An advantage to this method is that viruses can be dispensed intravascularly, thus evading antiviral immunity and being able to reach the tumor from a distance. Mesenchymal stromal cells loaded with Ad-D24RGD have been able to migrate to and infect intracerebral gliomas, whereas Ad-D24RGD alone was unable to do so.…”
Section: Gene Therapy For Brain Tumorsmentioning
confidence: 99%